Primary progressive freezing gait: case report Marcha congelada progressiva primária: relato de caso - Denise Hack Nicaretta; João Santos Pereira; Maria Lucia Vellutini Pimentel (Arquivos de Neuro-Psiquiatria)
The clinical features of the primary progressive freezing gait, a rare and distinct neurological entity, have been described in some articles. This paper describes this gait disorder affecting one patient, whose condition's long course provoked no postural instability. As stated in the literature, the pathophysiology of the primary progressive freezing gait still remains unclear, although the lack of response to levodopa therapy suggests a possible involvement of nondopaminergic pathways. Alteration in the visual perception may be a potential cause for the condition. Uma rara e distinta entidade neurológica, a marcha congelada progressiva primária, tem sido relatada na literatura. Descrevemos o caso de um paciente com este distúrbio da marcha que, apesar do longo curso da doença, não apresentava instabilidade postural. Como citado na literatura, a fisiopatologia desta condição permanece obscura, embora a falta de resposta à levodopa sugira uma possível participação de vias não dopaminérgicas. Alteração na percepção visual também pode estar envolvida na gênese desta afecção.